Use of complementary and alternative medicine among patients with acne vulgaris and factors perceived to trigger the disease: A multicentre cross-sectional study with 1571 patients - Kayiran, Melek Aslan; Karadag, Ayse Serap; Alyamac, Gokcen; Cemil, Bengu Cevirgen; Demirseren, Duriye Deniz; Demircan, Yuhanize Tas; Alpsoy, Erkan (Wolters Kluwer Medknow Publications, 2022)
Background: Acne vulgaris (AV) is among the common skin diseases for which patients refer to complementary and alternative medicine (CAM). Aims and Objectives: To investigate the approaches to CAM methods and factors believed to increase the disease in 1,571 AV patients. Materials and Methods: The sociodemographic characteristics of the patients and disease severity according to the Food and Drug Administration criteria were recorded. The Cardiff Acne Disability Index (CADI) was used to assess the impact of acne on the patient's life and the history of CAM use was noted. The patients also listed the factors that they thought worsened their disease and reported their gluten-free diet experiences. Results: Of all the patients, 74.41% had a history of using CAM methods. CAM use was significantly higher in women, patients with severe AV, those with a higher CADI score and non-smokers. As a CAM method, 66.37% of the patients reported having used lemon juice. The respondents most frequently applied CAM methods before consulting a physician (43.94%), for a duration of 0-2 weeks (38.97%). They learned about CAM methods on the internet (56.24%) and considered CAM methods to be natural (41.86%). The patients thought that food (78.55%) and stress (17.06%) worsened their disease. They considered that the most common type of food that exacerbated their symptoms was junk food (63.84%) and a gluten-free diet did not provide any benefit in relieving AV (50%). Conclusion: Physicians need to ask patients about their CAM use in order to be able to guide them appropriately concerning treatments and applications with a high level of evidence.
Keywords: Acne vulgaris; complementary and alternative medicine; dermatology; gluten; junk food